Implementation of Negotiation Text Learning Through Interactive Learning Media Based on Genially Applications in Vocational High Schools - Nurhidayah, Oktavia; Huda, Miftakhul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the application of interactive media using the Genially application in teaching negotiation texts at SMK Batik 2 Surakarta. The urgency of this research lies in the importance of integrating technology into learning, particularly in the digital era, to The research employed a qualitative approach with data collected from Indonesian language teachers and tenth-grade students of the Marketing Expertise Program. Data collection methods included interviews, observations, and documentation. The data were analyzed using thematic analysis, involving data reduction, theme categorization, and conclusion drawing. To ensure data validity and reliability, triangulation of sources and methods was conducted by comparing findings from interviews, observations, and documentation. Results: The findings revealed that the use of the Genially application in teaching negotiation texts at SMK Batik 2 Surakarta was highly relevant and aligned with the instructional needs of the subject. The media facilitated student engagement and contributed to a better understanding of the negotiation text material. Applications/Originality/Value: This study demonstrates that the Genially application serves as an effective technological tool to enhance students’ comprehension of negotiation texts in vocational high schools. It adds value by showcasing how interactive digital media can be successfully integrated into language instruction, thereby supporting the digital transformation of teaching methods and promoting more interactive, student-centered learning experiences.